STATISTICAL RESTORATION OF SECONDARY MINIMA DEPTHS FOR ECLIPSING VARIABLE STARS AND SPECIFICATION OF THEIR EVOLUTIONARY TYPES - Svirskaya, E. M. (Одеські астрономічні публікації, 2017)
30 unknown magnitudes of secondary minima depths for eclipsing variable stars are restored by ZET - method. Evolutionary types of some eclipsing variable stars arespecified on the basis of obtained data.